Investigating the relationship between the characteristics of the board of directors and the audit committee on the company 's performance - Leyla Bagherzadeh; Mohammadreza Vatanparast; Esmail Fadaei Kaloorazi (New Applied Studies in Management, Economics & Accounting, 2021)
This research, based on the theoretical foundations and literature of the subject, has investigated the relationship between the characteristics of the board of directors and the performance of companies listed on the stock exchange market. To accomplish this goal, 130 companies listed on the Tehran Stock Exchange have been selected as the study sample during 2014 to 2018 by the screening. Multivariate regression models have been used to analyse the data and test the hypotheses. Findings show that there is no significant relationship between the variables of the number of the board members and board independence with the company performance, but there is a significant relationship between the effectiveness of the audit committee and return on assets. According to the research results, for policymakers in financial markets to ensure maximum results, paying close attention to police implementation is recommended. Also, it is recommended the executives of the Tehran Stock Exchange to supervise the audit committees of companies through a systematic control mechanism, to increase the quality of effectiveness.